Determinan Variabel Yang Mempengaruhi IHSG Di Masa Pandemi Covid-19 - Nelly Ervina; Khairul Azwar (Jurnal Akuntansi dan Pajak, 2023)
The composite stock price index will show the general price movement of stocks listed on the stock exchange. The movement of JCI is caused by several factors, including macroeconomic factors. For this reason, the ability of investors to understand and predict macroeconomic conditions in the future is very useful in making profitable investment decisions. This study aims specifically to analyze the variables that affect the JCI during the Covid-19 pandemic. This research was conducted during the period January 2020 – June 2022 based on monthly inflation, exchange rate, TVA, and JCI data obtained from the Capital Market Directory. The sampling technique used in this study was saturated samples. The data analysis technique to be used is to use multiple and simple linear regression analysis. The results of the F test give the result that inflation, exchange rate and TVA have a positive and significant effect on the JCI. The results of the t-test showed that inflation and TVA had a significant positive effect on the JCI. Meanwhile, the exchange rate has a positive and insignificant effect on the JCI.